Development Of Software System For Detecting Defective Symbol On IC Chip Using Matrox Imaging Library - Azri, Maaspaliza (2004)
In semiconductor fabrication process, symbol or label inspection is one of the main processes that needs to be considered seriously. Errors may occur during the printing process of label or name on the integrated circuit chip (IC). If this occurs, the IC chip may have a wrong name. This will affect the credibility of the company who produces the IC chips. The problem mentioned above can be solved by providing a reliable detection system that is able to detect the errors printed on the IC chip. The symbol detection system that currently being implemented by the semiconductor industry suffers from over killed and escapes problems. This project presents the development a software system, which capable of detecting the defective characters printed on the IC chip using Active Matrox Imaging Library Release 7. The proposed system has an adjustable reading level that can solve the overkilled and escaped problems. It consists of a graphical user interface module, an inference engine, an image database, an ActiveMIL ActiveX control module, a Matrox Imaging Library module, an input image, and an output image. The proposed system is written in Visual Basic version 6 and it is interfaced with Active Matrox Imaging Library. The proposed system also has learning capability. It can store up to two different IC images at one time. The system was designed for off-line operation. The test results demonstrated that the proposed system performs according to its functions. It achieves 100% detection rate.